Assessment of livestock manure-derived hydrochar as cleaner products: Insights into basic properties, nutrient composition, and heavy metal content. (1st January 2022) - Fu, Haibin; Wang, Bingyu; Wang, Haihou; Liu, Hao; Xie, Huifang; Han, Lanfang; Wang, Ning; Sun, Xiaolong; Feng, Yanfang; Xue, Lihong
Abstract: Conversion of livestock manure to hydrochar through hydrothermal carbonization (HTC) could fix carbon and reduce pollution. The properties of hydrochar largely determined its application; thus, it is significant to comprehensively assess the manure-derived hydrochars (MHCs). However, relatively few systematic studies on MHCs are insufficient to support agricultural research on MHCs. This study investigated the basic properties, nutrient composition and speciation, and heavy metal content in pig/cattle manure and its MHCs (PCs and CCs). Results showed that MHCs were neutral and weakly acidic, which were milder than its alkalinity manure, and could not change the soil acidity too much when applied to the soil. After HTC, nitrogen (N) and phosphorus (P) contents were enriched in CCs with 3.47–21.5% N and 69.6–135% P, and in PCs with 74.1–132% P. MHCs prepared at higher temperature had stronger resistance to degradation due to rich ash content, which was conducive to carbon sequestration as soil remediation agents. Besides, the MHCs with rich ash content could also supplement macro/micronutrients for plant growth. More calcium-bound P content (2.26–2.44 times for PCs, 4.78–5.38 times for CCs) suggested that HTC promoted P fixation in MHCs, further reduced nutrient loss, and relieved the eutrophication. Most concentrated heavy metals in MHCs were still up to the biochar-based organic fertilizer standard, which could not increase heavy metal risk compared with manure. Overall, the MHCs as energy-saving and value-added products with sufficient and balanced nutrients and limited heavy metal pollution risk, which can yield valuable agricultural potential. This research would provide theoretical support for the agricultural utilization of MHCs. Graphical abstract: Image 1 Highlights: Hydrothermal carbonization (HTC) is conducive to reduce and recycle manures. Manure-derived hydrochars have sufficient nitrogen/phosphorus and high stability. HTC facilitates phosphorus fixation and reduces the risk of phosphorus loss. Enriched heavy metal in hydrochars does not rise environment risk compared to manures.